PENDAPATAN USAHA PENGGEMUKAN SAPI POTONG DI DESA PACAR KELING KECAMATAN KEJAYAN KABUPATEN PASURUAN - Asnah Asnah (BUANA SAINS, 2007)
Cut-cow fattening business has been developing for the last ten years due to increasing meat demand in line with increasing population. Such a business, however, is still faced by various constraints related to low capital from the breeders, lack of skills and experiences especially in cows’ health and weaknesses of local breeds. The aim of this research was to study the cost, revenue, income, efficiency and break even point of cut-cow fattening business. The study was conducted on farmers’ group of Sumber Rejeki, Pacar Keling, Kejayan District of Pasuruan Regency. The results showed that based on cots, revenue and income, the business was feasible as indicated by the revenue cost ratio of 1,2. The break even point of this business was 18,193 cows and Rp 10.107, 47/kg life weight